(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Objective: The purpose of the present research study was to develop sustained release (SR) tablet formulations for Losartan Potassium using HPMCK100M as a release retardant. Methods: Losartan Potassium is an antihypertensive agent angiotensin-II receptor blocker belongs to BCS class-II agent. SR tablets for Losartan Potassium were formulated using variable quantities of HPMCK100M and Xanthan Gum by direct compression method. quantities of polymers was chosen as independent variables, X1 and X2 respectively whereas, time required for dissolution 10% (t10%), 50% (t50%), 75% (t75%) and 90% (t90%) of drug from formulation were chosen as dependent variables. 9 formulations were prepared and evaluated for various pharmacopoeial tests. Results: The results reveals that all formulations were found to be within the acceptable limits and release rate profiles of all formulations were fitted to kinetic models. The statistical parameters were determined. Polynomial equations were developed for dependent variables. Validity of them was checked by countercheck formulations (C1, C2). According to SUPAC guidelines, formulation (F4) containing mixture of 10% HPMCK100M and 14% Xanthan gum, was found to be identical formulation (dissimilarity factor f1= 1.765, similarity factor f2= 86.735) to marketed product (COZAAR). Conclusion: Formulation F4 follows First order kinetics, Non-Fickian Diffusion Anomalous Transport. (n= 0.825).